A COMPREHENSIVE REVIEW OF FABRICATION AND CHARACTERIZATION METHODS OF HYDROXYAPATITE - LUNG, Claudiu; MARCONI, Daniel; FEHER, Tudor (Studia Universitatis Babeș-Bolyai Physica, 2023)
This synthesis article expands on the applications of hydroxyapatite (HA) coatings on titanium dioxide (TiO2) substrates for biomedical applications, focusing on the methods of deposition and their impact on the material’s properties. Various techniques, including sol-gel, electrochemical deposition and ultrasonic spray-pyrolysis are discussed because of their ability to enhance the mechanical resistance, biocompatibility and osteointegration of implants. The analysis methods used are X-Ray Diffraction (XRD), Scanning electron Microscopy (SEM) and Fourier Transform Infrared Spectroscopy (FTIR). They provide insights into the structural, chemical and physical characteristics of the HA coatings. The results indicate that these hybrid coatings significantly improve the performance and longevity of implants in orthopedic and dental applications.